Composite solid electrolyte and preparation method thereof

By using composite solid electrolytes in solid -state batteries, the fence structure and specific component ratio with vertical arranges solve the problem of low -level battery ionic conductivity and low lithium ion migration, and achieve more efficient battery performance.

CN119361817APending Publication Date: 2025-01-24AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411503622.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The low ion conductivity and lithium ion migration of solid-state batteries limit their fast charging and discharge capabilities and overall efficiency.

Method used

The fence structure with a composite solid electrolyte has a single -layer or multi -layer vertical arrangement, including lithium ion sieve, polymer, inorganic ceramic fillers and lithium salt, and prepared through 3D printing technology.

Benefits of technology

Effectively shorten the transportation path of lithium ions, improve the electrolyte ion conductivity and mechanical stability, and improve the fast charging power and overall efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361817A_ABST
    Figure CN119361817A_ABST
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte and a preparation method thereof, and belongs to the technical field of batteries, the composite solid electrolyte has a single-layer or multi-layer vertically arranged fence structure, and the composite solid electrolyte comprises the following components: a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt. The structure of the composite solid electrolyte provided by the invention is a fence structure imitating plant tissues, and the vertically arranged fence structure can effectively shorten the transportation path of lithium ions, effectively inhibit the volume expansion of the lithium ions in embedding and removing, and weaken the volume effect. Meanwhile, the composite solid electrolyte provided by the invention has a single-ion high-speed transport channel, and a lithium ion sieve in the composite solid electrolyte can enable the outer wall of a vertical arrangement structure of the electrolyte to have ion selectivity, so that anions can be effectively fixed, efficient transmission of lithium ions is realized, and the charge transmission efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a composite solid electrolyte and a preparation method thereof. Background Art

[0002] As an emerging battery technology, solid-state batteries are widely considered to be an important development direction of future battery technology due to their high energy density, long cycle life, excellent safety performance and potential low cost advantages. However, the ionic conductivity of solid electrolytes is much lower than that of liquid electrolytes, and there is even an order of magnitude difference in parameters such as ionic conductivity, which seriously limits the fast charging and discharging capabilities of solid-state batteries. On the basis of low ionic conductivity, the low lithium ion migration number will further affect the ion transmission efficiency of the electrolyte, thereby reducing the overall efficiency of the battery.

[0003] The composition and structural design of the material determine the performance of the solid electrolyte. Therefore, the ionic conductivity, chemical stability, mechanical stability and interface compatibility of the solid electrolyte can be improved by optimizing the composition and structure of the material. For example, the solid electrolyte with a sandwich structure design provided by the prior art, by sandwiching an inorganic solid electrolyte between polymer solid electrolytes, can achieve the effect of combining the advantages of organic and inorganic solid electrolytes; the solid electrolyte with a nanocomposite structure design provided by the prior art, by introducing a nanoscale organic phase into the inorganic skeleton to improve the performance of ion transmission; the solid electrolyte with a porous structure design provided by the prior art, by increasing the contact area between the electrolyte and the electrode material through the porous structure, the ion transmission efficiency is improved; and the solid electrolyte with a gradient structure design provided by the prior art, the gradient structure can balance the concentration distribution of lithium ions in the electrolyte, and avoid the local accumulation of lithium ions on the electrode surface to induce lithium dendrites.

[0004] Although the solid electrolytes with the above structural designs have played a good role in improving the performance of traditional solid electrolytes, the conductivity and migration efficiency of solid-state batteries are still not comparable to those of liquid batteries. Therefore, the preparation of solid electrolytes with high conductivity for single ion transport is still one of the urgent problems to be overcome in the development of high-speed and high-efficiency solid-state batteries. Summary of the invention

[0005] The main purpose of the present invention is to provide a composite solid electrolyte and a preparation method thereof, so as to optimize the ionic conductivity, ion transfer rate, chemical stability, mechanical stability and interface compatibility of the existing solid electrolyte.

[0006] In order to achieve the above object, the present invention provides a composite solid electrolyte, which has a single-layer or multi-layer vertically arranged fence structure, and the composite solid electrolyte includes the following components: a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt.

[0007] Furthermore, the composite solid electrolyte comprises the following components in parts by weight: 10 to 15 parts of lithium ion sieve, 60 to 100 parts of polymer, 5 to 15 parts of inorganic ceramic filler and 4 to 15 parts of lithium salt.

[0008] Furthermore, the lithium ion sieve is metal organic framework MOFs and / or covalent organic framework COFs.

[0009] Furthermore, the polymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyethylene oxide, polyvinylidene fluoride, polyvinyl chloride, polyvinyl alcohol, polyethyl acetate, polyethylene glycol divinyl ether or polycaprolactone.

[0010] Furthermore, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium trifluoromethanesulfonate and lithium bis(trifluoromethylsulfonyl)imide.

[0011] Furthermore, the inorganic ceramic filler is selected from one or more of lithium lanthanum zirconium oxide compounds, lithium lanthanum titanium oxide compounds, lithium aluminum titanium phosphate compounds or lithium aluminum germanium phosphate compounds.

[0012] Furthermore, the longitudinal dimensions of the vertically arranged fence structure units distributed on both sides of the composite solid electrolyte are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side.

[0013] Another aspect of the present invention provides a method for preparing the aforementioned composite solid electrolyte, comprising the following steps:

[0014] Designing a 3D model of a composite solid electrolyte structure using computer software, and importing the 3D model of the composite solid electrolyte structure into a 3D printer;

[0015] Weigh the lithium ion sieve, polymer, lithium salt and inorganic ceramic filler according to proportion;

[0016] Mixing a portion of the polymer, the lithium salt and the entire amount of the lithium ion sieve with an organic solvent to prepare an ink precursor liquid A;

[0017] Mixing another portion of the polymer, the lithium salt and the entire amount of the inorganic ceramic filler with an organic solvent to prepare an ink precursor liquid B;

[0018] The 3D printer uses independent dual nozzles to print the ink precursor A liquid and the ink precursor B liquid respectively according to a preset 3D model route to obtain a precursor of a composite solid electrolyte;

[0019] The precursor of the composite solid electrolyte is sequentially subjected to demoulding and thermal curing treatment to obtain the composite solid electrolyte.

[0020] Furthermore, the printing setting parameters of the ink precursor liquid A and the ink precursor liquid B include: a printing rate of 100-500 mm / s; a printing pressure of 5-15 MPa; a printing temperature of room temperature; and a printing method of layer-by-layer 3D printing.

[0021] Furthermore, the organic solvent is selected from one or more of formamide, N,N-dimethylformamide, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate or dimethoxymethane.

[0022] Furthermore, in the ink precursor liquid A and the ink precursor liquid B, the mass fraction of the organic solvent is independently 60 to 75%.

[0023] Furthermore, the temperature of the heat curing treatment is 30 to 80° C., and the time of the heat curing treatment is 2 to 8 hours.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The composite solid electrolyte provided by the present invention has a single-layer or multi-layer vertically arranged fence structure, and its structure is modeled after the fence structure of plant tissue. This vertically arranged fence structure can effectively shorten the transport path of lithium ions, effectively inhibit the volume expansion of lithium ions during insertion and extraction, and weaken the volume effect.

[0026] 2. According to the arrangement rules of plant palisade tissue, when the composite solid electrolyte has multiple layers of vertically arranged palisade structures, the designed composite solid electrolyte has smaller vertically arranged palisade structure units on both sides, which can further regulate the ion flux between the electrolyte and the electrode, effectively construct a good electrode-electrolyte interface, and improve the cyclic stability of the electrolyte; and the design in which the large-sized vertically arranged palisade structure units on the inner side are sandwiched by the small-sized vertically arranged palisade structure units on both sides can effectively neutralize the stress generated inside the electrolyte and improve the mechanical stability of the electrolyte.

[0027] 3. The composite solid electrolyte proposed in the present invention has a single ion (lithium ion) high-speed transport channel, wherein the lithium ion sieve in the composite solid electrolyte can make the outer wall of the vertically arranged structure of the electrolyte have ion selectivity, can effectively fix anions, realize the efficient transmission of lithium ions, and improve the charge transfer efficiency; in addition, the interior of the composite solid electrolyte structural unit is filled with inorganic ceramic fillers to further improve the ionic conductivity of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the structure of a composite solid electrolyte in one embodiment of the present invention is shown;

[0029] Figure 2 The results of impedance testing of button-type symmetrical batteries assembled with composite solid electrolytes according to Example 1 of the present invention are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0030] Figure 3 The results of the impedance test before and after polarization of the Li|SPEs|Li test element assembled with the composite solid electrolyte of Example 1 of the present invention using the constant potential polarization method are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0031] Figure 4 The it curve graph obtained by testing the Li|SPEs|Li test element assembled with the composite solid electrolyte according to Example 1 of the present invention under a polarization bias voltage of 5 mV is shown;

[0032] Figure 5 The results of impedance testing of button-type symmetrical batteries assembled with composite solid electrolytes according to Example 2 of the present invention are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0033] Figure 6 The results of the impedance test before and after polarization of the Li|SPEs|Li test element assembled with the composite solid electrolyte of Example 2 of the present invention using the constant potential polarization method are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0034] Figure 7 The it curve graph obtained by testing the Li|SPEs|Li test element assembled with the composite solid electrolyte according to Example 2 of the present invention under a polarization bias voltage of 5 mV is shown;

[0035] Figure 8 The results of impedance testing of button-type symmetrical batteries assembled with composite solid electrolytes according to comparative example 1 of the present invention are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0036] Fig. 9 The results of the impedance test before and after polarization of the Li|SPEs|Li test element assembled with the composite solid electrolyte of Comparative Example 1 of the present invention using the constant potential polarization method are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0037] Fig.10 It curve graph of the Li|SPEs|Li test element assembled with the composite solid electrolyte of Comparative Example 1 of the present invention obtained by testing under a polarization bias of 5 mV is shown;

[0038] Fig.11 The results of impedance testing of button-type symmetrical batteries assembled with composite solid electrolytes according to comparative example 2 of the present invention are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0039] Fig.12 The results of the impedance test before and after polarization of the Li|SPEs|Li test element assembled with the composite solid electrolyte of Comparative Example 2 of the present invention using the constant potential polarization method are shown; wherein the abscissa is the real part and the ordinate is the imaginary part;

[0040] Fig.13 The it curve graph obtained by testing the Li|SPEs|Li test element assembled with the composite solid electrolyte of Comparative Example 2 of the present invention under a polarization bias of 5 mV is shown. DETAILED DESCRIPTION

[0041] It should be noted that, in the case of no conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or the intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope. The present invention will be described in detail below in conjunction with the embodiments.

[0042] In order to achieve the above-mentioned purpose, a first aspect of an embodiment of the present invention provides a composite solid electrolyte, which has a single-layer or multi-layer vertically arranged fence structure, and the composite solid electrolyte includes the following components: a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt.

[0043] The composite solid electrolyte of the present invention has a single-layer or multi-layer vertically arranged fence structure, which can effectively shorten the transport path of lithium ions, and can effectively inhibit the volume expansion of lithium ions during insertion and extraction, thereby weakening the volume effect. At the same time, the composite solid electrolyte of the present invention includes a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt, and the components work in coordination, wherein the lithium ion sieve can make the outer wall of the vertically arranged structure of the composite solid electrolyte have ion selectivity, effectively fix anions, realize efficient transmission of lithium ions, and improve charge transfer efficiency, and the inorganic ceramic filler filled in the interior of the composite solid electrolyte can further improve the ionic conductivity of the electrolyte, and the combination of the organic polymer and the inorganic lithium salt can simultaneously have both excellent ionic conductivity and mechanical properties.

[0044] The present invention adopts two methods, namely, specially designing the structure of the solid electrolyte and optimizing the material components of the composite solid electrolyte, so that the composite solid electrolyte of the present invention can effectively optimize the ion conductivity, ion transfer rate, chemical stability, mechanical stability and interface compatibility of the existing solid electrolyte.

[0045] In a preferred embodiment of the present invention, the composite solid electrolyte includes the following components by weight: 10 to 15 parts of lithium ion sieve, 60 to 100 parts of polymer, 5 to 15 parts of inorganic ceramic filler and 4 to 15 parts of lithium salt. The present invention precisely controls the lithium ion sieve, inorganic ceramic filler and polymer within the above-mentioned proportion range, and the lithium ion sieve and inorganic ceramic filler can effectively improve the ionic conductivity of the electrolyte. At the same time, the appropriate proportion of polymer enhances the molecular flexibility, improves the mechanical properties of the solid electrolyte, and improves the interface compatibility of the solid electrolyte. By controlling the proportion of lithium salt in the electrolyte so that it has better dispersibility in the electrolyte, the rate performance of the electrolyte is further improved.

[0046] In summary, the present invention can achieve the optimal state of ion conductivity, ion transfer rate, chemical stability, mechanical stability and interface compatibility of the composite solid electrolyte by precisely controlling the ratio of lithium ion sieve, polymer, inorganic ceramic and lithium salt in the composite solid electrolyte.

[0047] In order to further improve the comprehensive performance of the composite solid electrolyte, in some preferred embodiments of the present invention, the lithium ion sieve is a metal organic framework MOFs and / or a covalent organic framework COFs; the polymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyethylene oxide, polyvinylidene fluoride, polyvinyl chloride, polyvinyl alcohol, polyethyl acetate, polyethylene glycol divinyl ether or polycaprolactone; the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium trifluoromethanesulfonate or lithium bis(trifluoromethylsulfonyl)imide; the inorganic ceramic filler is selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum titanium phosphate or lithium aluminum germanium phosphate.

[0048] In a specific embodiment of the present invention, the composite solid electrolyte has a single-layer vertically arranged fence structure, and the composite solid electrolyte includes the following components: a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt.

[0049] In a preferred embodiment of the present invention, the composite solid electrolyte has a multi-layered fence structure, and the longitudinal dimensions of the vertically arranged fence structure units distributed on both sides of the composite solid electrolyte are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side.

[0050] When the composite solid electrolyte has a multi-layer vertically arranged fence structure, the designed composite solid electrolyte has smaller vertically arranged fence structure units on both sides, which can further regulate the ion flux between the electrolyte and the electrode, effectively construct a good electrode-electrolyte interface, and improve the cycle stability of the electrolyte; and the design in which the large-sized vertically arranged fence structure units on the inner side are sandwiched by the small-sized vertically arranged fence structure units on both sides can effectively neutralize the stress generated inside the electrolyte and improve the mechanical stability of the electrolyte.

[0051] According to a second aspect of the present invention, there is provided a method for preparing the composite solid electrolyte, comprising the following steps:

[0052] Designing a 3D model of a composite solid electrolyte structure using computer software, and importing the 3D model of the composite solid electrolyte structure into a 3D printer;

[0053] Weigh the lithium ion sieve, polymer, lithium salt and inorganic ceramic filler according to proportion;

[0054] Mixing a portion of the polymer, the lithium salt and the entire amount of the lithium ion sieve with an organic solvent to prepare an ink precursor liquid A;

[0055] Mixing another portion of the polymer, the lithium salt and the entire amount of the inorganic ceramic filler with an organic solvent to prepare an ink precursor liquid B;

[0056] The 3D printer uses independent dual nozzles to print the ink precursor A liquid and the ink precursor B liquid respectively according to a preset 3D model route to obtain a precursor of a composite solid electrolyte;

[0057] The precursor of the composite solid electrolyte is sequentially subjected to demoulding and thermal curing treatment to obtain the composite solid electrolyte.

[0058] The composite solid electrolyte of the present invention uses 3D printing technology to imitate the blade palisade organization to prepare a composite solid electrolyte with a single-layer or multi-layer vertically arranged palisade structure. First, a 3D model with a single-layer or multi-layer vertically arranged palisade structure is designed, and an ink precursor A liquid and an ink precursor B liquid containing composite solid electrolyte components are prepared; then the ink precursor A liquid and the ink precursor B liquid are 3D printed to obtain the precursor of the composite solid electrolyte; wherein the ink precursor A liquid is printed to form the external skeleton structure of the composite solid electrolyte, and the ink precursor B liquid is printed and filled in the interior of the external skeleton structure of the composite solid electrolyte, and finally, after demolding and thermal curing treatment steps, the mechanical and electrochemical stability of the electrolyte is improved to obtain a composite solid electrolyte. The 3D printing preparation method of the present invention is an effective means for preparing the high-performance composite solid electrolyte of the present invention, and the prepared composite solid electrolyte has a single ion high-speed transport channel, which can selectively and efficiently transport lithium ions.

[0059] In a preferred embodiment of the present invention, the printing setting parameters of the ink precursor A liquid and the ink precursor B liquid include: a printing rate of 100-500 mm / s; a printing pressure of 5-15 MPa; a printing temperature of room temperature; and a printing method of layer-by-layer 3D printing. The present invention optimizes the parameters of the 3D printer so that the prepared composite solid electrolyte has a higher yield rate.

[0060] In some preferred embodiments of the present invention, the organic solvent is selected from one or more of formamide, N,N-dimethylformamide, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate or dimethoxymethane. In the ink precursor A liquid and the ink precursor B liquid, the mass fraction of the organic solvent is independently 60-75%. The present invention dissolves the printing substrate by adding a certain proportion of organic solvent, so that the printing substrate can be smoothly ejected at a preset temperature and pressure during the printing process.

[0061] In order to further improve the mechanical and electrochemical stability of the electrolyte, in a preferred embodiment of the present invention, the temperature of the heat curing treatment is 30 to 80° C., and the time of the heat curing treatment is 2 to 8 hours. In the demolding process of the present invention, a water-soluble or degreasing demolding agent is selected for demolding according to the specific properties of the printed ink precursor solution.

[0062] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0063] Example 1

[0064] A composite solid electrolyte, such as Figure 1 As shown, it has three layers of vertically arranged fence structures, the longitudinal dimensions of the vertically arranged fence structure units distributed on both sides are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side, and includes a skeleton structure imitating plant fence tissue and ceramic particles (i.e., inorganic ceramic fillers) filled inside the skeleton structure. The following specific components are included: 15 parts of lithium ion sieve (ZIF-8), 90 parts of polymer (polyvinylidene fluoride-hexafluoropropylene copolymer), 15 parts of inorganic ceramic fillers (lithium lanthanum zirconium tantalum oxide LLZTO) and 15 parts of lithium salt (lithium bistrifluoromethanesulfonyl imide LiTFSI).

[0065] The preparation method is as follows:

[0066] Step 1: Design a 3D model of a composite solid electrolyte having a three-layer vertically arranged fence structure using computer design software, and import the 3D model of the composite solid electrolyte structure into a 3D printer.

[0067] Step 2: Weigh 1 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI and 6 g of polyvinylidene fluoride-hexafluoropropylene copolymer, add them to 20 mL of N,N-dimethylformamide, and magnetically stir at 60°C for 3 hours to obtain a mixed solution; weigh 1.5 g of ZIF-8 and add it to the above mixed solution, and continue magnetically stirring at 60°C for 2 hours to obtain ink precursor A liquid.

[0068] Step 3: Weigh 0.5 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, 3 g of poly(vinylidene fluoride)-hexafluoropropylene copolymer, and 1.5 g of LLZTO powder, add them into 10 mL of N,N-dimethylformamide, and stir them magnetically at 60° C. for 3 h to obtain ink precursor liquid B.

[0069] Step 4: Use a 3D printer to perform independent dual-nozzle printing. For the ink precursor A liquid, set the nozzle pressure to 10Mpa, the printing rate to 200mm / s, the printing temperature to room temperature (25°C), and print layer by layer. For the ink precursor B liquid, set the nozzle pressure to 10Mpa, the printing rate to 300mm / s, the printing temperature to room temperature (25°C), and print layer by layer; according to the set program, print all the oil on the substrate to obtain a precursor of the composite solid electrolyte, then demold the above-mentioned composite solid electrolyte precursor, and finally place it in a 60°C vacuum oven for thermal curing for 8h to obtain a composite solid electrolyte.

[0070] The composite solid electrolyte was used to prepare a button-type symmetrical battery and the impedance test was carried out under the conditions of an amplitude of 5mV and a frequency range of 0.1 to 1000000 Hz. The results are as follows Figure 2 As shown in the figure, the impedance value of the composite solid electrolyte is 47.8 ohm. Combined with the solid electrolyte thickness L = 0.1 cm, the effective contact area S is 2.01 cm 2 , calculated by the formula σ=L / SR, the ionic conductivity σ=1.04×10 -3 S / cm.

[0071] The prepared electrolyte was combined into a basic test element in the form of Li|SPEs|Li by constant potential polarization method. The test was performed using Chenhua CHI660E electrochemical workstation. The impedance of the electrolyte in the initial state was tested within the test frequency range of 0.01HZ-100KHZ, and the impedance value at this time was recorded as R0. The battery was then placed under a polarization bias of 5mV to measure the it curve, and the initial state current I0 and steady-state current Is were recorded. The impedance of the battery was then tested again within the same frequency range and recorded as R S The test data can be found in Figure 3 and Figure 4, as can be seen from the figure, R0 = 73.58ohm, Rs = 90.18ohm, I0 = 55.34uA, Is = 42.1uA, and according to the formula The lithium ion migration number of the composite solid electrolyte was calculated, and it was found that the lithium ion migration number of the composite solid electrolyte was 0.59.

[0072] Example 2

[0073] A composite solid electrolyte, such as Figure 1 As shown, it has three layers of vertically arranged fence structures, the longitudinal dimensions of the vertically arranged fence structure units distributed on both sides are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side, and includes a skeleton structure imitating plant fence tissue and ceramic particles (i.e., inorganic ceramic fillers) filled inside the skeleton structure. The following specific components are included: 10 parts of lithium ion sieve (ZIF-8), 60 parts of polymer (polyvinylidene fluoride-hexafluoropropylene copolymer), 5 parts of inorganic ceramic fillers (lithium lanthanum zirconium tantalum oxide LLZTO) and 4 parts of lithium salt (lithium bistrifluoromethanesulfonyl imide LiTFSI).

[0074] The preparation method is as follows:

[0075] Step 1: Design a 3D model of a composite solid electrolyte having a three-layer vertically arranged fence structure using computer design software, and import the 3D model of the composite solid electrolyte structure into a 3D printer.

[0076] Step 2: Weigh 0.2 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI and 3 g of polyvinylidene fluoride-hexafluoropropylene copolymer, add them to 10 mL of N,N-dimethylformamide, and magnetically stir at 60°C for 3 hours to obtain a mixed solution; weigh 1 g of ZIF-8 and add it to the above mixed solution, and continue magnetically stirring at 60°C for 2 hours to obtain ink precursor A liquid.

[0077] Step 3: Weigh 0.2 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, 3 g of poly(vinylidene fluoride)-hexafluoropropylene copolymer, and 0.5 g of LLZTO powder, add them into 10 mL of N,N-dimethylformamide, and stir them magnetically at 60° C. for 3 h to obtain ink precursor liquid B.

[0078] Step 4: Use a 3D printer to perform independent dual-nozzle printing. For the ink precursor A liquid, set the nozzle pressure to 10Mpa, the printing rate to 200mm / s, the printing temperature to room temperature (25°C), and print layer by layer. For the ink precursor B liquid, set the nozzle pressure to 10Mpa, the printing rate to 300mm / s, the printing temperature to room temperature (25°C), and print layer by layer; according to the set program, print all the oil on the substrate to obtain a precursor of the composite solid electrolyte, then demold the above-mentioned composite solid electrolyte precursor, and finally place it in a 60°C vacuum oven for thermal curing for 8h to obtain a composite solid electrolyte.

[0079] The composite solid electrolyte was used to prepare a button-type symmetrical battery and the impedance test was carried out under the conditions of an amplitude of 5mV and a frequency range of 0.1-1000000Hz. The test results are as follows Figure 5 As shown in the figure, the impedance value of the composite solid electrolyte is 61.7 ohm. Combined with the solid electrolyte thickness L = 0.1 cm, the effective contact area S is 2.01 cm 2 , according to the formula Calculated, σ = 8.06 × 10 -4 S / cm.

[0080] The prepared electrolyte was combined into a basic test element in the form of Li|SPEs|Li by constant potential polarization method. The test was performed using Chenhua CHI660E electrochemical workstation. The impedance of the electrolyte in the initial state was tested within the test frequency range of 0.01HZ-100KHZ, and the impedance value at this time was recorded as R0. The battery was then placed under a polarization bias of 5mV to measure the it curve, and the initial state current I0 and steady-state current Is were recorded. The impedance of the battery was then tested again within the same frequency range and recorded as R S The test data can be found in Figure 6 and Figure 7 As can be seen from the figure, R0 = 130.2ohm, Rs = 179.2ohm, I0 = 33.36uA, Is = 22.7uA, and according to the formula The lithium ion migration number of the composite solid electrolyte was calculated, and it was found that the lithium ion migration number of the composite solid electrolyte was 0.48.

[0081] Comparative Example 1

[0082] A composite solid electrolyte, such as Figure 1As shown, it has three layers of vertically arranged fence structures, the longitudinal dimensions of the vertically arranged fence structure units distributed on both sides are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side, including a skeleton structure imitating plant fence tissue and ceramic particles (i.e., inorganic ceramic fillers) filled inside the skeleton structure. The following specific components are included: 100 parts of polymer (polyvinylidene fluoride-hexafluoropropylene copolymer), 15 parts of inorganic ceramic fillers (lithium lanthanum zirconium tantalum oxide LLZTO) and 13 parts of lithium salt (bistrifluoromethanesulfonyl imide lithium LiTFSI). Compared with the embodiment, the components of the composite solid electrolyte do not contain lithium ion sieves.

[0083] The preparation method is as follows:

[0084] Step 1: Design a 3D model of a composite solid electrolyte having a three-layer vertically arranged fence structure using computer design software, and import the 3D model of the composite solid electrolyte structure into a 3D printer.

[0085] Step 2: Weigh 1 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI and 7.5 g of poly(vinylidene fluoride)-hexafluoropropylene copolymer, add them into 20 mL of N,N-dimethylformamide, and stir them magnetically at 60° C. for 3 h to obtain ink precursor liquid A.

[0086] Step 3: Weigh 0.3 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, 2.5 g of poly(vinylidene fluoride)-hexafluoropropylene copolymer, and 1.5 g of LLZTO powder, add them into 10 mL of N,N-dimethylformamide, and stir them magnetically at 60° C. for 3 h to obtain ink precursor liquid B.

[0087] Step 4: Use a 3D printer to perform independent dual-nozzle printing. For the ink precursor A liquid, set the nozzle pressure to 10Mpa, the printing rate to 200mm / s, the printing temperature to room temperature (25°C), and print layer by layer. For the ink precursor B liquid, set the nozzle pressure to 10Mpa, the printing rate to 300mm / s, the printing temperature to room temperature (25°C), and print layer by layer; according to the set program, print all the oil on the substrate to obtain a precursor of the composite solid electrolyte, then demold the above-mentioned composite solid electrolyte precursor, and finally place it in a 60°C vacuum oven for thermal curing for 8h to obtain a composite solid electrolyte.

[0088] The composite solid electrolyte was used to prepare a button-type symmetrical battery and the impedance test was carried out under the conditions of an amplitude of 5mV and a frequency range of 0.1-1000000Hz. The test results are as follows Figure 8 As shown in the figure, the impedance value of the composite solid electrolyte is 115.6 ohm. Combined with the solid electrolyte thickness L = 0.1 cm, the effective contact area S is 2.01 cm 2 , according to the formula Calculated, σ = 4.30 × 10 -4 S / cm.

[0089] The prepared electrolyte was combined into a basic test element in the form of Li|SPEs|Li by constant potential polarization method. The test was performed using Chenhua CHI660E electrochemical workstation. The impedance of the electrolyte in the initial state was tested within the test frequency range of 0.01HZ-100KHZ, and the impedance value at this time was recorded as R0. The battery was then placed under a polarization bias of 5mV to measure the it curve, and the initial state current I0 and steady-state current Is were recorded. The impedance of the battery was then tested again within the same frequency range and recorded as R S The test data can be found in Fig. 9 and Fig.10 , as can be seen from the figure, R0 = 145.71ohm, Rs = 162.52ohm, I0 = 31.87uA, Is = 23.61uA, and according to the formula The lithium ion migration number of the composite solid electrolyte was calculated, and it was found that the lithium ion migration number of the composite solid electrolyte was 0.23.

[0090] Comparative Example 2

[0091] A solid electrolyte membrane, which has a common single-layer solid electrolyte structure and does not have a vertically arranged fence structure, includes the following specific components: 15 parts of lithium ion sieve (ZIF-8), 90 parts of polymer (polyvinylidene fluoride-hexafluoropropylene copolymer), 15 parts of inorganic ceramic filler (lithium lanthanum zirconium tantalum oxide LLZTO) and 15 parts of lithium salt (lithium bistrifluoromethanesulfonyl imide LiTFSI).

[0092] The preparation method is as follows:

[0093] Step 1: Weigh 1.5 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, 9 g of poly(vinylidene fluoride)-hexafluoropropylene copolymer, 1.5 g of LLZTO and 1.5 g of ZIF-8, add them into 30 mL of N,N-dimethylformamide, and stir them magnetically at 60° C. for 3 h to obtain a precursor solution.

[0094] Step 2: pour the above precursor solution into a glass culture dish to cast into a film, dry it in a constant temperature drying oven at 60° C. for 8 hours, and obtain a solid electrolyte membrane after the organic solvent evaporates.

[0095] The solid electrolyte membrane was tested for ionic conductivity and lithium ion migration number. The button-type symmetrical battery prepared using the electrolyte was tested for impedance under the conditions of an amplitude of 5 mV and a frequency range of 0.1-1000000 Hz. The results are as follows Fig.11As shown in the figure, the impedance value of the composite solid electrolyte is 758.4 ohm. Combined with the solid electrolyte thickness L = 0.1 cm, the effective contact area S is 2.01 cm 2 , according to the formula Calculated, σ = 6.56 × 10 -5 S / cm.

[0096] The prepared electrolyte was combined into a basic test element in the form of Li|SPEs|Li by constant potential polarization method. The test was performed using Chenhua CHI660E electrochemical workstation. The impedance of the electrolyte in the initial state was tested within the test frequency range of 0.01HZ-100KHZ, and the impedance value at this time was recorded as R0. The battery was then placed under a polarization bias of 5mV to measure the it curve, and the initial state current I0 and steady-state current Is were recorded. The impedance of the battery was then tested again within the same frequency range and recorded as R S The test data can be found in Fig.12 and Fig.13 , as can be seen from the figure, R0 = 205.4ohm, Rs = 249.2ohm, I0 = 22.13uA, Is = 15.27uA, and according to the formula The lithium ion migration number of the composite solid electrolyte was calculated, and it was found that the lithium ion migration number of the composite solid electrolyte was 0.26.

[0097] The above-described embodiments only represent the embodiments of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. The present invention can also be implemented in other specific ways or other specific forms without departing from the gist or essential features of the present invention. Therefore, the described embodiments should be regarded as illustrative rather than restrictive in any respect. The scope of the present invention should be described by the attached claims, and any changes equivalent to the intention and scope of the claims should also be included in the scope of the present invention.

Claims

1. A composite solid electrolyte, characterized in that: The composite solid electrolyte has a single-layer or multi-layer vertically arranged fence structure, and the composite solid electrolyte includes the following components: a lithium ion sieve, a polymer, an inorganic ceramic filler and a lithium salt.

2. The composite solid electrolyte according to claim 1, characterized in that The composite solid electrolyte comprises the following components in parts by weight: 10 to 15 parts of lithium ion sieve, 60 to 100 parts of polymer, 5 to 15 parts of inorganic ceramic filler and 4 to 15 parts of lithium salt.

3. The composite solid electrolyte according to claim 2, characterized in that: The lithium ion sieve is a metal organic framework MOFs and / or a covalent organic framework COFs; The polymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyethylene oxide, polyvinylidene fluoride, polyvinyl chloride, polyvinyl alcohol, polyethyl acetate, polyethylene glycol divinyl ether or polycaprolactone.

4. The composite solid electrolyte according to claim 2, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonyl)imide; The inorganic ceramic filler is selected from one or more of lithium lanthanum zirconium oxide compounds, lithium lanthanum titanium oxide compounds, lithium aluminum titanium phosphate compounds or lithium aluminum germanium phosphate compounds.

5. The composite solid electrolyte according to any one of claims 1 to 4, characterized in that The longitudinal dimensions of the vertically arranged fence structure units distributed on both sides of the composite solid electrolyte are smaller than the longitudinal dimensions of the vertically arranged fence structure units on the inner side.

6. A method for preparing a composite solid electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Designing a 3D model of a composite solid electrolyte structure using computer software, and importing the 3D model of the composite solid electrolyte structure into a 3D printer; Weigh the lithium ion sieve, polymer, lithium salt and inorganic ceramic filler according to proportion; Mixing a portion of the polymer, the lithium salt and the entire amount of the lithium ion sieve with an organic solvent to prepare an ink precursor liquid A; Mixing another portion of the polymer, the lithium salt and the entire amount of the inorganic ceramic filler with an organic solvent to prepare an ink precursor liquid B; The 3D printer uses independent dual nozzles to print the ink precursor A liquid and the ink precursor B liquid respectively according to a preset 3D model route to obtain a precursor of a composite solid electrolyte; The precursor of the composite solid electrolyte is sequentially subjected to demoulding and thermal curing treatment to obtain the composite solid electrolyte.

7. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The printing setting parameters of the ink precursor liquid A and the ink precursor liquid B include: The printing rate is 100-500mm / s; the printing pressure is 5-15MPa; the printing temperature is room temperature; and the printing method is layer-by-layer 3D printing.

8. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: The organic solvent is selected from one or more of formamide, N,N-dimethylformamide, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, methyl formate or dimethoxymethane.

9. The method for preparing a composite solid electrolyte according to claim 6, characterized in that: In the ink precursor liquid A and the ink precursor liquid B, the mass fraction of the organic solvent is independently 60 to 75%.

10. The method for preparing a composite solid electrolyte according to any one of claims 6 to 9, characterized in that: The temperature of the heat curing treatment is 30 to 80° C., and the time of the heat curing treatment is 2 to 8 hours.